Obesity and overweight in market workers and their associated factors - Rios, Marcela Andrade (2021)
Objective: To estimate the prevalence of overweight and obesity in market workers in Guanambi and to verify its association with sociodemographic and labor characteristics. Method: The study was carried out through a census and cross-sectional study developed with data obtained from a larger research baseline called "Work accidents at street vendors and health and work conditions: prospective study". The data collection took place between January and March 2018 through the application of forms and the verification of anthropometric data of weight and height. The analysis was carried out with the aid of the IBM SPSS software, descriptive, with calculations of relative and absolute frequencies, and Person's Chi-square test using p ≤ 0.05 as statistical significance. Results: It was observed that 33.3% of the population was overweight and 28.6% (122) presented obesity, resulting in 66.5% overweight workers. Of which, 71.5% (173) were female, between the 41-59 age group, 77.5%, with schooling up to elementary school 73.3% and 65.0% of workers who reported a life profile negative. Regarding the type of merchandise sold, the highest percentage was in products in nature 65.8%. As for comorbidities, Diabetes Mellitus and Hypertension, 65.4% and 61.4% were overweight, respectively. Conclusion: Modifiable and non-modifiable factors were found in workers with higher frequencies of obesity and overweight. The importance of health promotion actions with such workers is pointed out, aiming to minimize potential health risks.